Gender Performance Practice and Pathet Interpretation in Miling: Gendhing Kethuk 4 Awis Minggah 8 in Pelog Pathet Nem - Anggara Wisnu Wardana; Wahyu Thoyyib Pambayun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2026)
This study examines gender performance practice (garap gender) in Miling, a gendhing kethuk 4 awis minggah 8 in pelog pathet nem, with particular attention to the musical strategies employed to negotiate the modulation from slendro pathet manyura to pelog pathet nem. This topic warrants scholarly attention due to the limited literature addressing gender performance practice within the context of modal and pathet transitions in this composition. The study aims to analyze the forms and principles of garap gender used in interpreting the balungan structure and the pathet characteristics embedded within the piece. A qualitative research design was employed, utilizing observation, literature review, and interviews as data collection techniques. The analysis was guided by Rahayu Supanggah’s concept of garap, focusing on the dimensions of pathet interpretation (tafsir patet), cengkok interpretation (tafsir cengkok), wiledan, dynamics, and rambatan. The findings reveal that the gender performance practice in Miling does not adhere rigidly to the characteristics of a single principal pathet. The presence of balungan structures encompassing both pathet nem and pathet sanga requires performers to adapt their cengkok interpretations according to contextual musical demands. Consequently, the continuity of the gending’s musical character is maintained through a creative negotiation between balungan structure, principal pathet orientation, and the practical conventions of garap gender.